2001
DOI: 10.1590/s0100-73862001000100001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle morphology on the mechanical and thermo-mechanical behavior of polymer composites

Abstract: Fiber reinforced polymer composites have been used in many applications, such as in automobile, aerospace and naval industries, due basically to their high strength-to-weight and modulus-to-weight, among other properties. Even though particles are usually not able to lead to the level of reinforcement of fibers, particle reinforced polymer composites have been proposed for many new applications due to their low cost, easy fabrication and isotropic properties. In this work, polymer composites were prepared by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 7 publications
2
12
0
1
Order By: Relevance
“…2b and 2d). Earlier it was demonstrated that higher aspect ratio of reinforcing agents affected more pronouncedly the viscoelastic behaviour of the systems, by imposing constraints to the mobility of the polymer chains [33]. The relatively isometric glass particles used in the present study are expected do not disturb much the flow behaviour.…”
Section: Resultsmentioning
confidence: 65%
“…2b and 2d). Earlier it was demonstrated that higher aspect ratio of reinforcing agents affected more pronouncedly the viscoelastic behaviour of the systems, by imposing constraints to the mobility of the polymer chains [33]. The relatively isometric glass particles used in the present study are expected do not disturb much the flow behaviour.…”
Section: Resultsmentioning
confidence: 65%
“…Fibras são notoriamente capazes de reforçar matrizes poliméricas, enquanto partículas podem não contribuir substancialmente como reforço [5,6] . No entanto, partículas são mais abundantes e menos onerosas do que fibras, o que tem motivado a busca por sistemas de reforço de plásticos à base de material particulado [7,8] .…”
Section: Introductionunclassified
“…Relaxation occurs whenever polymer chains rearrange themselves to adopt either a lower energy conformation or to fill free volume. The shape of the Cole–Cole plot is affected by factors such as differences in the structure of segmental units within a polymer chain, heterogeneities due to inherent processing characteristic features including (1) molecular weight distribution, (2) free volume distribution, (3) filler concentration, (4) degree of crystallinity and thermomechanical history . Nonsymmetrical semi‐circle curve of the Cole–Cole plot for the polymer and polymer composites is indicative of the system's heterogeneity…”
Section: Resultsmentioning
confidence: 99%